Preliminary investigation on seismic risk of hospital functions in Lima - Palomino J. (2019)
Hospitals are vital assets to communities when a disaster strikes, and some functions are essential for an adequate emergency response. This paper presents the initial results of a study on the earthquake risk to hospital functions in Lima, Peru. The study draws upon the World Bank Lima hospital database and shows that buildings containing operating rooms and emergency care units are particularly vulnerable to earthquakes. Hospital services are grouped and ranked according to their importance in a post disaster context. This information is then crossed with seismic capacity data to evaluate simplified risk indices. The results show that 66% of the operating theatres and 45% of the emergency rooms have a high level of risk. These results will provide insight for a retrofit prioritization scheme for health infrastructure in Lima, focusing on hospital functions and function interdependencies rather than the buildings alone. © 2019, National Technical University of Athens. All rights reserved.